CFIUS and the cost of risk aversion - Stephen Heifetz (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2024)
As the U.S. government has become increasingly intolerant of national security risks sometimes attendant to foreign investment, Stephen Heifetz suggests the government should consider the costs of that risk avoidance and should alter its approach.
Keywords: 330